1964
DOI: 10.1037/h0043537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and multiple enforced intercopulatory intervals on the sexual behavior of male rats.

Abstract: Male rats copulated through 2 Ejaculatory Series under 3 conditions: ad lib., or normal, uninterrupted intercourse; single enforced interval, in which the copulating pair was separated for a period of time after either the 1st or 4th intromission of each Series; and multiple enforced intervals, in which the animals were separated following every intromission. 1st Series intromission frequencies in single and multiple enforced interval sessions decreased with increases in duration of enforced interval. Mount fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0
1

Year Published

1967
1967
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 11 publications
2
28
0
1
Order By: Relevance
“…In accordance with previous studies (Larsson, 1956;Bermant, 1964), the results of Exp. I show that artificial prolongation of the interintromission intervals considerably reduces the number of mounts and intromissions required for ejaculation.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous studies (Larsson, 1956;Bermant, 1964), the results of Exp. I show that artificial prolongation of the interintromission intervals considerably reduces the number of mounts and intromissions required for ejaculation.…”
Section: Discussionsupporting
confidence: 93%
“…These studies have shown that increasing the duration of the enforced intervals up to 5 minutes decreases the number of intromissions needed to reach ejaculation. These data suggest that limited availability of the female increases male arousal and lowers the ejaculatory threshold [32]. Under MPCA conditions, a similar and even greater effect was observed.…”
Section: Discussionsupporting
confidence: 56%
“…In a pioneering study, Larsson showed that the number of intromissions needed to reach first ejaculation could be significantly reduced by separating the copulating pair after each intromission for a period of time greater than the normal intercopulatory interval [21,29,30]. This effect, called enforced interval effect, has been further corroborated by other authors [31,32]. These studies have shown that increasing the duration of the enforced intervals up to 5 minutes decreases the number of intromissions needed to reach ejaculation.…”
Section: Discussionmentioning
confidence: 82%
“…Among males, a prolonged III, similar to that which occurs during paced mating, results in the expression or because each stimulus is more intense under paced than of intromissions which are significantly longer (approximately 600 ms) nonpaced mating conditions (8). As shown in the present study, than those exhibited by males who are able to intromit ad lib (approxiimmediate-early gene expression can be a useful tool in determinmately 500 ms);(41)(42)(43). In this experiment, long-duration intromissions ing which of these elements of mating stimulation have relevance were expected when males were allowed only to intromit with the experimental female at approximately 100 s IIIs.…”
mentioning
confidence: 51%